REPRESENTASI PENGETAHUAN PERANCANGAN BERBASIS ONTOLOGI SEBAGAI DASAR SISTEM PENDAMPINGAN MENU DIET VEGETARIAN - , SATRIA ADI SURYA WIJAYA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Advances in information technology can be utilized as a facility to design vegetarian diet menu assistance system. Knowledge representation could be applied into this system using the ontology in design and implementation. An appropriate ontology that describes the domain models of nutritional needs and food for the vegetarians had not been discovered an ontology that until the end of 2013, whereas ontology could be used to describe structural concept of the expert system. This research implements the way to build and manage knowledge based on the ontology model. Consistent ontology model helps to manage the data into knowledge. In this research, the target object is vegetarian diet because a balanced vegetarian diet can provide many health benefits including reduced risk of disease. Vegetarian diet menu assistance system can be separated into two parts, the back-end and the front-end. This research scope focuses on the back-end that includes three phases such as the ontology design by adopting a methodology that combined two methodologies, namely Gruninger and Fox and modified METHONTOLOGY, ontology consistency test using Pellet Reasoner, and testing of the ontology with SPARQL query. The design of an ontology-based knowledge representation as the vegetarian diet menu assistance system has been developed by Protégé. Ontology formalization in Protégé has been done based on the preliminary draft model of ontology and the ontology development results. This research shows that the developed ontology domain model has successfully described the nutritional needs and food menu for vegetarians after doing some testing process. The first test is consistency test of ontology using Pellet Reasoner shows the consistency of the ontology because there are no conflicting conclusion from the definition of valid input. The second test is testing of the ontology with SPARQL query that has been able to doing search and processing the data of the ontology results with different variation of queries based on 7 competency questions and 3 system test scenarios. The front-end part to process ontology results has not yet been developed in this research which can be continued in the future research.